Effects of hypertonic saline preloading in sub arachnoid blockade for transurethral resection of prostate - A comparative study - Islam, Amirul; Siddique, Md Rafayet Ullah; Kamal, Md Mustafa; Banik, Debabrata; Akhtaruzzaman, AKM; Hye, Md Abdul (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Hypertonic solution is used to combat hypotension in sub-arachnoid block during trans urethral resection of prostate. Aims and objectives: To compare the effect of 3% sodium chloride solution with that of 0.9% sodium chloride solution, to combat sub-arachnoid block induced hypotension in trans urethral resection of prostate. Methods: A total number of sixty patients ASA grade I & II were selected randomly in two groups , thirty in each group. Group A received 15ml/kg of 0.9% NaCl solution and group B 4ml/kg of 3% NaCl solution as a preload. Sub arachnoid block performed at the L3/4 interspace in the sitting position. Heart rate, mean arterial pressure, amount of ephedrine, amount of used additional I/V normal saline, serum electrolytes and level of sensory block were observed. Results: Mean arterial pressure was differed significantly at late hours ie, 50min, 60min (P<0.001). Incidence of hypotension was 43% in group A, 16% in group B and was significant (p<0.05). Less additional I/V fluid was required in group B and difference was significant (P<0.05). Low doses of ephedrine was needed in group B and was highly significant (P<0.001). Conclusion: Preloading of hypertonic solution is superior to isotonic solution in trans urethral resection of prostate under sub arachnoid block. DOI: http://dx.doi.org/10.3329/jbsa.v22i2.18145 Journal of BSA, 2009; 22(2): 66-71